Frequency of Cardiac-Toxicity in Patient Treated with Anthracycline, An Institutional Perspective - Muhammad Tariq, Muhammad Ibrahim, Saqib Raza Khan, Sehrish Sarwar Baloch, Mehwish Shahzadi, Yasmin Abdul Rashid, Muhammad Jawad Zahid, Mohammad Daanyaal Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Cancer now affects more than one in three people in their lifetime. Cancer remains the leading cause of death in many countries. Anthracycline-based chemotherapy has played an important part in the current age of cancer treatment, with earlier diagnosis and novel medicines. Objective: To find out the frequency of cardiac-toxicity (cardiomyopathy) in patient treated with anthracycline Methodology: This Descriptive Study was carried out at the Oncology department of Hayatabad Medical Complex, Peshawar for duration of six months from 20 Dec, 2019 to 20 Jun, 2020. Patients attending the medical oncology department of Hayatabad Medical Complex, Peshawar were included in the study. Demographic data like age, sex was collected in the pre-designed Performa. The patients were sent for echocardiography which was done by cardiologist and ejection fraction was noted. The patients suitable for treatment on anthracycline were started with standard doses for his/her carcinoma which were for leukemia 25mg/m2 weekly for 1 months, for lymphoma (NHL) 50mg/m2 after every 21 days for 4.2 months, for breast carcinoma 60mg/m2 after every 21 days for 2.8 months. Results: As per frequencies and percentages for anthracycline induced cardiomyopathy, 31 (15.0%) patients had anthracycline induced cardiomyopathy. Conclusion: Our research shows that although preventing chronic cardiotoxicity may be challenging, prolong infusion methods for anthracyclines offer a reduced risk, and novel liposomal formulations of doxorubicin may provide less cardiotoxicity as compared to conventional doxorubicin.